Mechanical Loss in Multiferroic Materials at High Frequencies: Friction and the Evolution of Ferroelastic Microstructures. (6th May 2013) - Zhao, Z.; Ding, X.; Lookman, T.; Sun, J.; Salje, E. K. H.
<x xml:space="preserve">Abstract</x> Energy absorption in multiferroic materials stems typically from strain relaxation which can be strong even when no extrinsic defects exist in the material. Computer simulations of a simple two‐dimensional model on a generic, proper ferroelastic material identify the dissipative mechanisms associated with the dynamical motion as: a) advance and retraction of needle‐shaped twin domains and, b) movement of kinks inside twin boundaries. Both movements involve friction losses. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>